Prevalence, Treatment, and Unmet Needs of Migraine in the Middle East: A Systematic Review - Taoufik Alsaadi; AbuBakar Al Madani; Mohammed Alhatou; Mona Nada; Abdulrazaq Albilali; Ahmed Al-Qassabi; Hegab Mohamed; Haytham Mohamed; Rowan El Masry; Ghaidaa Ahmed Saifuddin; Suhail Abdullah AlRukn (Pain and Therapy)
Abstract Introduction Migraine is a debilitating neurological disorder characterized by recurrent throbbing, moderate-to-severe headaches that disrupt daily chores, leisure, and social activities of patients, impacting their overall quality of life (QoL). Despite the high disease burden, there is a scarcity of data on migraines within the Middle East (ME) region. Thus, a systematic literature review (SLR) was conducted to examine epidemiological data, treatment patterns, QoL, and unmet needs regarding migraines in the ME region. Methods Electronic searches were carried out using the MEDLINE® and Embase® databases via the OvidSP® platform for articles published prior to April 2024. The inclusion and exclusion criteria for the selection of studies were based on the Patients, Intervention, Comparator, Outcomes, and Study design framework, which identified 42 studies. Results The prevalence of migraines reported from the region ranged between 2.6 and 32%, and the average age of patients with migraines reported in these studies ranged from 27 to 37.5 years. The data indicated a gender disparity in migraine prevalence, with women exhibiting a 2- to 2.5-fold higher prevalence. Common comorbidities reported were depression, anxiety, and irritable bowel disease. Migraines significantly impact patients' physical and emotional well-being, leading to disabilities and loss of productivity. The most common triggers of migraines were sleep disorders, dietary habits, and stress. The current treatment landscape for acute migraines encompasses anti-inflammatory agents, analgesics, triptans, ditans, calcitonin-gene-related peptides, and antiemetics. However, migraines in the region are often underestimated, underreported, and undertreated. Several unmet needs persist in the region, including delayed referral along with delayed diagnosis, misdiagnosis, poor treatment adherence, limited accessibility to treatments, and a lack of awareness among health care providers and patients. Conclusions The SLR highlights knowledge gaps in clinical aspects and the treatment of migraines and enables clinicians to make informed decisions to ensure optimal patient outcomes in diverse clinical settings.